Experimental and Theoretical Design Methodology of Hemispherical Shells under Extreme Static Loading - Galiev, Sh.U.; Blachut, J.; Skurlatov, E.D.; Panova, O.P.; Moltschaniwskyj, G.; Cui, Z. (Проблемы прочности, 2004)
We present mathematical dependences describing
the research results for metal half-sperical
shells subjected to static loading by external
pressure. We studied the behavior and conditions
of static buckling of empty, styrofoam-
filled and geometrically imperfect shells.
Regression equations in the form of incomplete
cubic polinomials are derived. In planes of governing
parameters we plot isolines, analysis of
which makes it possible to draw qualitative and
quantitative conclusions on the externally pressurized
shell behavior. Представлены математические зависимости, описывающие результаты исследований
металлических полусферических оболочек при статическом нагружении внешним давлением.
При этом исследовались поведение и условия потери устойчивости как пустотелых, так и
заполненных пенопластом оболочек с геометрическими несовершенствами. Получены уравнения
регрессии в виде неполных кубических полиномов. В плоскостях определяющих параметров
построены изолинии, анализ которых позволяет сделать качественные и количественные
выводы о поведении оболочек в условиях нагружения внешним давлением. Представлено математичні залежності, що описують результати досліджень
металевих напівсферичних оболонок при статичному навантаженні зовнішнім
тиском. При цьому досліджувалися поведінка й умови втрати стійкості
як пустотілих, так і заповнених пенопластом оболонок із геометричною
недосконалістю. Отримано рівняння регресії у вигляді неповних кубічних
поліномів. У плоскостях визначальних параметрів побудовано ізолінії, аналіз
яких дозволяє зробити якісні і кількісні висновки щодо поведінки оболонок
в умовах навантаження зовнішнім тиском.